Health Education Intervention on HIV/AIDS Prevention Behaviors among Health Volunteers in Healthcare Centers: An Applying the Theory of Planned Behavior. Issue 45 (8th August 2019) - Siuki, Hadi Alizadeh; Peyman, Nooshin; Vahedian-Shahroodi, Mohammad; Gholian-Aval, Mahdi; Tehrani, Hadi
Abstract: Present study aims to investigate the impact of health education intervention on improving HIV/AIDS preventive behaviors among Health volunteers in Torbat-e Heydarieh Iran. 120 Health volunteers were involved in this quasi-experimental study (60 participants in intervention group and 60 participants in control group). Data collection tool was a questionnaire based on theory of planned behavior along with demographic questions which was applied before and 2 month after intervention. Data analysis was conducted using SPSS16 with descriptive analysis, and analytical tests (independent t -test, correlation coefficient) were conducted at 5% significance level. The findings of the study showed no significant difference between two groups in terms of mean scores of knowledge, attitude, performance, behavioral intention, and behavioral control before intervention ( p  > 0.05). But a significant difference was observed between two groups after the health education intervention ( p  < 0.05). Health education intervention based on theory of planned behavior, regarding AIDS disease preventive behavior, significantly affects Health volunteers. Therefore, according to behavior theory, such educations lead to positive changes in AIDS preventive behaviors.